Distribution and growth in Latin America in an era of structural reform - Morley, Samuel (International Food Policy Research Institute, 2001)
The first section of this paper reviews the most recent evidence on inequality in 18 Latin American countries and shows that in all but four the changes in inequality over the 1990s were small and insignificant. The distribution depends on the ownership and rate of return on assets, particularly human capital. The paper summarizes various recent papers as well as the author’s recent work on the impact of structural reforms on inequality. Finally, the paper presents evidence of a significant slowdown in the growth rate and argues that given this fact and the insensitivity of the distribution to feasible policy measures, the main problem facing the region at present is not how to improve the distribution but rather how the increase the growth rate.